A Nuclear Magnetic Resonance Spectroscopy as a Method for Evaluation of In Vivo Poly-l-Lactide Biodegradation Kinetics From Stent-Polymer Matrices: An Experimental Study Utilizing Porcine Model of In-Stent Restenosis. (January 2016) - Orlik, Bartłomiej; Buszman, Piotr P.; Krauze, Agata; Gąsior, Paweł; Desperak, Piotr; Pająk, Jacek; Kasperczyk, Janusz; Janas, Adam; Jelonek, Michał; Handzlik-Orlik, Gabriela; Buszman, Paweł E.; Milewski, Krzysztof
Objectives: We aimed to comprehensively evaluate poly-lactide polymer degradation and sirolimus release kinetics from a drug-eluting stent matrix in the in vivo setting using a nuclear magnetic resonance (NMR) method. Methods: In 22 domestic swine, 18 biodegradable polymer-only coated stents (BPSs) and 36 biodegradable polymer-coated sirolimus-eluting stents (BP-SES) were implanted in coronary arteries with 115% overstretch. The animals were sacrificed at 1, 3, 7, 14, 28, and 56 days following baseline procedures. Vessel segments with BPS were harvested to evaluate polymer degradation with a NMR method, whereas BP-SES to analyze sirolimus tissue uptake and retention. Additionally, 8 BP-SES were implanted for histological analysis for 90 days of follow-up. Results: The NMR showed a gradual absorption of the polymer over the 6 consecutive time points, from 5.48 µg of the polymer on the stent at 1-day follow-up, through 4.33 µg at 3 days, 3.16 µg at 7 days, 2.42 µg at 14 days, 1.92 µg at 28 days to 1.24 µg in the last day of the study. The curve of polymer degradation corresponds well with the pharmacokinetic profile of sirolimus eluted from its surface and measured at identical time points. In histopathology, at 90 days, complete healing and biocompatibility were reported. Conclusions: The utilization of NMR method for BP absorption kinetics evaluation is a useful tool, which may be widely adopted to test other biodegradable implants. Further, it may substantially improve their safety and efficacy by facilitating programmed polymer and drugs elution.